Palaeofacies and biomarker characteristics of Paleogene to Neogene rocks in the Makassar Straits, Indonesia - Sutadiwiria, Yarra; Hamdani, Ahmad Helman; Sendjaja, Yoga Andriana; Haryanto, Iyan; Siahaan, Yeftamikha; Siahaan, Mordekhai (Geologos, 2019)
Borehole K-1 is an exploratory well that was drilled in the North Makassar Basin (West Sulawesi) in 2011. Gas chromatography (GC) and gas chromatography-mass chromatography (GC-MS) analyses have been conducted on extracts from well cuttings from the Paleogene to Neogene interval in order to investigate the characteristics of biomarkers present. Although the well was drilled with oil-based mud and gas chromatographic analysis reveals that the alkane fractions are heavily contaminated, detailed investigation of biomarkers in these rock extracts and comparison with biomarkers in the oil-based mud has revealed that, while there are hopane and sterane biomarkers in the mud, there are also a discrete set of biomarkers that are indigenous to the rocks. These include oleanane, bicadinanes, taraxastane and other higher-plant-derived triterpanes. The presence of these compounds in environments that range from bathyal to marginal marine and even to lacustrine, shows the extent of reworking of terrestrial material into aquatic settings in this region during the Paleogene and Neogene and provides further evidence of a predominance of terrestrial material, even in deep-marine settings, with little ‘in-situ’ material noted. These findings have important implications for the use of biomarkers as indicators of palaeoenvironment in both source rocks and oils.